2021
DOI: 10.1021/acsomega.1c02205
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Wettability of Coal with Different Metamorphism Treated by Surfactants for Coal Dust Control

Abstract: Wet dedusting is the main coal dust suppression technique in coal mines, and coal wettability is the main factor affecting dust suppression efficiency. To investigate the main factors affecting the coal wettability and improve it, the coal–water contact angle was used as an index to characterize the coal wettability, and the wettability of six coal samples with different metamorphic degree was studied by analyzing the relationship between the physicochemical properties and the contact angle. To improve the coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 51 publications
(71 reference statements)
0
14
0
Order By: Relevance
“… 10 , 11 To lower the surface tension and enhance the wettability of coal, wetting agents can be incorporated into water. 12 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 11 To lower the surface tension and enhance the wettability of coal, wetting agents can be incorporated into water. 12 14 …”
Section: Introductionmentioning
confidence: 99%
“…During manufacturing and transportation of coal from mines, massive coal dust is produced, which causes pneumoconiosis in coal miners. Pneumoconiosis is a preventable but incurable lung disease, which not only causes chest pain but also causes significant complications such as chronic cor pulmonale and respiratory failure. Nowadays, the main dust removal method used in coal mines is spray dust removal. Water is ineffective in wetting coal dust since its surface tension reaches 72.8 mN/m, while for coal, it is 45 mN/m at critical wetting. , To lower the surface tension and enhance the wettability of coal, wetting agents can be incorporated into water. …”
Section: Introductionmentioning
confidence: 99%
“…Due to the high surface tension of water (72 mN/m), it is often ineffective in the process of wetting the coal surface. To reduce the surface tension of water and improve its wetting efficiency, surfactants are often added to water …”
Section: Introductionmentioning
confidence: 99%
“…To reduce the surface tension of water and improve its wetting efficiency, surfactants are often added to water. 19 Most of the early studies showed that the wetting ability of water was significantly improved after the use of surfactants, which was conducive to improving the dust suppression effect. Fan et al 20 and Xu et al 21 found that the addition of a surfactant to water can promote the solution properties, reduce surface tension and the contact angle of the solution, increase the wettability of the solution to coal dust, and thus improve the dust removal efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation